THE INFLUENCE OF THE SCHOOL OF MOVEMENT, PARENTS' OCCUPATION, AND FAMILY ENVIRONMENT ON ENTREPRENEURIAL INTERESTS OF STUDENTS IN SENIOR HIGH SCHOOL - Sudarwati, Ninik; Chalimah, Chalimah; Nurhayati, Dies (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
To establish a good business, a strong entrepreneurial spirit is needed. SMAN 1, SMAN 2, SMAN 3 Jombang students can be supported by the education of the driving school project, parents' work, and family environment, which can shape the mindset and interest of each student in the world of entrepreneurship. Based on this phenomenon, the authors are interested in conducting research by taking the title: "The Effect of the Driving School Project, Parents' Occupation and Family Environment on the Entrepreneurial Interest of Students of SMAN 1, SMAN 2, and SMAN 3 Jombang ". This study aimed to determine the effect of the driving school project, Parents' Employment, and Family Environment, on the Entrepreneurial Interest of SMAN 1, SMAN 2, and SMAN 3 Jombang students. This research uses a quantitative research design with a linear regression analysis to examine the relationship between variables X1, X2, and X3 based on the well-being of students in the Jombang schools.  The results showed that 1) the driving school project variable did not affect the entrepreneurial interest of SMAN 1, SMAN 2, and SMAN 3 Jombang students. 2) The variable of parents' occupation affects the entrepreneurial interest of students of SMAN 1, SMAN 2, and SMAN 3 Jombang. 3) Family environment variables affect the entrepreneurial interest of SMAN 1, SMAN 2, and SMAN 3 Jombang students. 4) The variables of driving school projects, parents' work, and the family environment simultaneously and positively affect the variable of entrepreneurial interest of students of SMAN 1, SMAN 2, and SMAN 3 Jombang. Author's suggestions: 1) The school must add and provide Facilities for driving school project activities. 3) The family must provide support for children's entrepreneurial desires.